Hubungan Penilaian Skor Puji Rohyati dengan Hasil Kehamilan di Puskesmas Mlonggo Jepara - Aini, Syifa Nur; Hidayah, Noor; Suwarto, Tri (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study was to determine the relationship between Puji Rohyati's score and high-risk pregnancies in the Mlonggo Community Health Center (Puskesmas) in Jepara. This quantitative study used a case-control design and a cross-sectional approach. The study was conducted at the Mlonggo Community Health Center in Jepara Regency. The population in this study were mothers who gave birth in 2024 within the Mlonggo Community Health Center's area, with a sample of 346 cases drawn using a total sampling technique. Data were analyzed using the chi-square test. Most mothers giving birth in the Mlonggo Community Health Center's area (174) had abnormal deliveries (50.3%) and 212 had high-risk pregnancies (61.3%). There was a significant association between Puji Rohyati's score and high-risk pregnancies, with a p-value <0.001 <sig α = 0.05 (OR 20.545, 95% CI 11.220-37.618). Pregnant women and their families need to improve their understanding of the importance of early detection of pregnancy risk factors through the Puji Rohyati scoring system.